A new typology of electoral violence: insights from Indonesia - Harish, S. P. (Terrorism and political violence, 2019)
Existing literature on election violence has focused on how violence suppresses voter participation or shapes their preferences. Yet, there are other targets of election violence beyond voters who have so far received little attention: candidates and government agencies. By intimidating rival candidates into dropping out of the race, political hopefuls can literally reduce the number of competitors and increase their likelihood of winning. Likewise, aspiring candidates can target government agencies perceived to be responsible for holding elections to push for electorally beneficial decisions. In this paper, we introduce a new typology of electoral violence and utilize new data of election violence that occur around executive elections in Indonesia from 2005 through 2012. The types of violence we identified differ in these ways: a) Of all cases of electoral violence observed in this article, most incidents were targeted towards candidates and government bodies; b) candidates are generally targeted before elections, whereas voter-targeting incidents are spread out evenly before and after elections and government-targeted violence tends to occur afterwards; c) pre-election violence is concentrated in formerly separatist areas, but post-election violence is more common in districts with prior ethnocommunal violence. These distinctions stress the importance of examining when and why different strategies are adopted.